Vulnerability to extreme heat in Metropolitan Phoenix: Spatial, temporal, and demographic dimensions - CHOW, Winston T. L. (Institutional Knowledge at Singapore Management University, 2012)
This study assessed the spatial distribution of vulnerability to extreme heat in 1990 and 2000 within metropolitan Phoenix based on an index of seven equally weighted measures of physical exposure and adaptive capacity. These measures were derived from spatially interpolated climate, normalized differential vegetation index, and U.S. Census data. From resulting vulnerability maps, we also analyzed population groups living in areas of high heat vulnerability. Results revealed that landscapes of heat vulnerability changed substantially in response to variations in physical and socioeconomic factors, with significant alterations to spatial distribution of vulnerability especially between eastern and western sectors of Phoenix. These changes worked to the detriment of Phoenix's Hispanic population and the elderly concentrated in urban-fringe retirement communities.